Unseen jungle : the microbes that secretly control our world - Spicer Rice, Eleanor (Spicer Rice, Eleanor. Your hidden life, 2023)
"Did you know that you're surrounded by microbes? They're on your body, in your body, and on every body! In fact, only about half of our bodies' cells are human cells--the rest are microbes. From the ways they help us digest our food to the ways they control critters and creatures (zombie flies, anyone?), microbes form an unseen jungle around us. Complete with zany, gross facts, hilarious and sometimes disgusting illustrations, and interviews with real researchers, this is your close-up view of the microbe drama unfolding in your world every day." -- Back cover.